2021
DOI: 10.1532/hsf.4259
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes of Patients Incidentally Confirmed with Covid-19 After Cardiac Surgery

Abstract: Background: The aim of this study was to investigate the clinical outcomes of cardiac surgery in patients who were incidentally diagnosed with Covid-19 in the postoperative period. Patients and methods: We performed 826 open cardiac surgeries in five tertiary centers. Most of the surgeries were elective coronary artery bypass grafting (CABG) (93.8%). A preoperative RT-PCR test and transcutaneous oxygen saturation were routinely investigated prior to surgery. We also investigated whether the patients already re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Finally, in this pandemic era, several viral postoperative cases of pneumonia have been ascribed to COVID-19 in patients that resulted RT-PCR test negative before cardiac surgery; immunologic disorders by the use of extracorporeal circulation, physiologic distress, and anesthesia would be responsible for COVID-19 activation during the incubation period [ 41 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Finally, in this pandemic era, several viral postoperative cases of pneumonia have been ascribed to COVID-19 in patients that resulted RT-PCR test negative before cardiac surgery; immunologic disorders by the use of extracorporeal circulation, physiologic distress, and anesthesia would be responsible for COVID-19 activation during the incubation period [ 41 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…In that same study, fatal outcomes were associated with decreased levels of serum albumin, and an open surgical procedure, the oxygen desaturation at the time of the COVID-19 diagnosis, and a PCR cycle threshold (Ct) value <20 were related to mortality (14). Furthermore, in their study on patients who underwent cardiac surgery and were then incidentally detected with COVID-19 post-surgery, Uysal et al (15) Table II reported a mortality rate of 20.7%, while in that same study, increased neutrophil and decreased lympocyte counts were associated with poor outcomes. Tabourin et al (16), in a post-operative assessment of the nosocomial transmission of COVID-19 following robotic surgery for urinary and gynecological cancer, as well as Bacalbasa et al (17) in a post-operative assessment of the nosocomial transmission of COVID-19 following surgery for ovarian cancer, found low mortality rates.…”
Section: Discussionmentioning
confidence: 95%
“…In a multi-center study consisting of 826 patients, the incidence of postoperative COVID-19 was reported as 5.8% after cardiac surgery. [ 1 ]…”
Section: Introductionmentioning
confidence: 99%
“…In a multi-center study consisting of 826 patients, the incidence of postoperative COVID-19 was reported as 5.8% after cardiac surgery. [1] The number of studies on the outcomes of COVID-19 occurring in the recovery period of open-heart surgery is very limited. [2] In the present study, we aimed to examine the effect of COVID-19 on the healing process of patients undergoing open-heart surgery.…”
mentioning
confidence: 99%